Crime Intelligent Security Control Robot Investigation System - Chandran, M; Vinothramkumar, B (International Journal of Computer Sciences and Engineering, 2025)
This researching Fingerprint based identification is one of the most mature & proven technique compared to the biometric technique. Fingerprints are classified as rolled, plain & latent fingerprints. However, even today, a fully automated latent fingerprint matching system has not been developed. However, even today, a fully automated latent fingerprint matching system has not been developed. Matching latent fingerprints over rolled or plain fingerprints is difficult task. The reason behind this is nothing but presence of noise and non-linear distortion in latent prints. Matching latent fingerprints over rolled or plain fingerprints is difficult task. An CIESs should be designed as a criminal investigation decision support system (CIDSS), a reasoning process based on production rules. we using image processing tool box for identify the criminals finger print ,If one decides to use only one year of crime data for detailed analysis then an analyst must spend 1.5 million minutes. As Per Regional Crime Analysis Program (RECAP), If one decides to use crime data for detailed analysis then an analyst